TP53 Status as a Determinant of Pro- vs Anti-Tumorigenic Effects of Estrogen Receptor-Beta in Breast Cancer. (16th April 2019) - Mukhopadhyay, Utpal K; Oturkar, Chetan C; Adams, Christina; Wickramasekera, Nadi; Bansal, Sanjay; Medisetty, Rajesh; Miller, Austin; Swetzig, Wendy M; Silwal-Pandit, Laxmi; Børresen-Dale, Anne-Lise; Creighton, Chad J; Park, Jun Hyoung; et al.
Abstract: Background: Anti-tumorigenic vs pro-tumorigenic roles of estrogen receptor-beta (ESR2) in breast cancer remain unsettled. We investigated the potential of TP53 status to be a determinant of the bi-faceted role of ESR2 and associated therapeutic implications for triple negative breast cancer (TNBC). Methods: ESR2-TP53 interaction was analyzed with multiple assays including the in situ proximity ligation assay. Transcriptional effects on TP53-target genes and cell proliferation in response to knocking down or overexpressing ESR2 were determined. Patient survival according to ESR2 expression levels and TP53 mutation status was analyzed in the basal-like TNBC subgroup in the Molecular Taxonomy of Breast Cancer International Consortium (n = 308) and Roswell Park Comprehensive Cancer Center (n = 46) patient cohorts by univariate Cox regression and log-rank test. All statistical tests are two-sided. Results: ESR2 interaction with wild-type and mutant TP53 caused pro-proliferative and anti-proliferative effects, respectively. Depleting ESR2 in cells expressing wild-type TP53 resulted in increased expression of TP53-target genes CDKN1A (control group mean [SD] = 1 [0.13] vs ESR2 depletion group mean [SD] = 2.08 [0.24], P = .003) and BBC3 (control group mean [SD] = 1 [0.06] vs ESR2 depleted group mean [SD] = 1.92 [0.25], P = .003); however, expression of CDKN1A (control group mean [SD] = 1 [0.21] vs ESR2 depleted group mean [SD] = 0.56 [0.12], P = .02) and BBC3 (control group mean [SD] = 1 [0.03] vs ESR2 depleted group mean [SD] = 0.55 [0.09], P = .008) was decreased in cells expressing mutant TP53. Overexpressing ESR2 had opposite effects. Tamoxifen increased ESR2-mutant TP53 interaction, leading to reactivation of TP73 and apoptosis. High levels of ESR2 expression in mutant TP53-expressing basal-like tumors is associated with better prognosis (Molecular Taxonomy of Breast Cancer International Consortium cohort: log-rank P = .001; hazard ratio = 0.26, 95% confidence interval = 0.08 to 0.84, univariate Cox P = .02). Conclusions: TP53 status is a determinant of the functional duality of ESR2. Our study suggests that ESR2-mutant TP53 combination prognosticates survival in TNBC revealing a novel strategy to stratify TNBC for therapeutic intervention potentially by repurposing tamoxifen.